2015
DOI: 10.1121/1.4921272
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic beamforming through a thin plate using vibration measurements

Abstract: The aim of this paper is to propose a methodology to localize acoustic sources from the measurement of airborne induced vibrations of a thin structure. Targeted applications are the identification of acoustic sources through a thin wall, with a potential filtration of the incident field, which may be of practical interest, for instance, when identifying exterior acoustic sources from the inside of a moving vehicle. Two methods are coupled here to achieve this purpose: the Force Analysis Technique (FAT), used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…In addition to loading identification problems, the force analysis technique was extended to identify mechanical parameters such as Young's modulus or the structural loss factor (Ablitzer et al, 2014). Another use of this technique was suggested by (Leclère and Picard, 2015). In their work, a loudspeaker to be localized was placed in a semi-anechoic room, this room being coupled to a reverberant room.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to loading identification problems, the force analysis technique was extended to identify mechanical parameters such as Young's modulus or the structural loss factor (Ablitzer et al, 2014). Another use of this technique was suggested by (Leclère and Picard, 2015). In their work, a loudspeaker to be localized was placed in a semi-anechoic room, this room being coupled to a reverberant room.…”
Section: Introductionmentioning
confidence: 99%
“…Another alternative might be the use of a vibrating structure (e.g. an thin plate) equipped with accelerometers [19]. It has been shown that the structure acts as a low-pass filter in the wavenumber domain, thus filtering out components with high wavenumbers associated to flow-induced noise.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the CFAT method has been recently implemented for beamforming applications based on vibration measurements. 10 The parietal acoustic field exciting a baffled plate is identified from vibration measurements (using CFAT), and then used as an input for standard beamforming codes. The approach has been validated experimentally for a pure acoustic load (without flow).…”
Section: Introductionmentioning
confidence: 99%